Legal Protection for the Public in the Implementation of CRS and FATCA in Improving Account Opening Compliance at Bank Indonesia - Kambey, Yanti Ivone; Pieris, John; Silalahi, Fernando; Saragi, Paltiada (Jurnal Indonesia Sosial Sains, 2025)
This research examines the legal protection for the public in implementing the Common Reporting Standard (CRS) and the Foreign Account Tax Compliance Act (FATCA) at Bank Indonesia. The increasing need for transparency in financial transactions highlights the importance of compliance in bank account openings. FATCA aims to combat tax evasion by requiring foreign financial institutions to report accounts held by U.S. taxpayers. However, this poses challenges to Indonesia’s banking secrecy laws, particularly Pasal 40 of the Undang-Undang Perbankan, which protects customer information. The study explores the implications of these regulations on customer trust and the operational readiness of Indonesian banks to meet international standards. Additionally, it evaluates the cooperation between Indonesia and the United States in enforcing FATCA and the CRS framework, emphasizing the need for regulatory adaptation to ensure compliance without compromising customer confidentiality. The findings indicate that while CRS and FATCA enhance transparency, they also necessitate careful consideration of legal protections for customers to maintain their trust in financial institutions. This research contributes to understanding the intersection of international tax compliance and local banking regulations, providing insights for policymakers and financial institutions in Indonesia.